Italianness, Creoleness and Tango in the 1905 Armonía Magazine (Revista Argentina de Musicología, 2024)
This article aims to provide an initial analytical exploration of Armonía, a magazine mainly dedicated to distributing scores for mandolin or violin with guitar accompaniment in Buenos Aires in 1905. Its circulation context is marked, on the one hand, by strong identity debates —both political and artistic— between the criollo (native-born Argentine) and Italian leadership in the Río de la Plata region; and on the other hand, by the burgeoning mass culture of Buenos Aires, determined by both criollo aesthetics and the prominence of immigrants. Armonía was directed by the Italo-Argentine mandolinist and tango composer Próspero Cimaglia (1876-1933) and brought together a diverse audience distributed across the national territory. In the reading proposed here, supported by the analysis of editorial discourse, the represented musical genres, and Cimaglia's trajectory, this study reveals the magazine's link with identity tensions. It aligned in certain aspects with Italianità, sharing certain values with this program and promoting a canon of Italian-Argentine masters. While at the same time maintaining links with more syncretic interaction models, characteristic of popular art. From the contextualized study of the magazine, the importance of the mandolin in these debates emerges as a symbol of Italian cultural capital.
Keywords: journals; periodicals; music magazines; Italian migration; mandolin; Próspero Cimaglia